Substituent effects on the ring-chain tautomerism of some 1,3-oxazolidine derivatives - Pihlaja, Kalevi; Juhász, Márta; Kivelä, Henri; Fülöp, Ferenc (Rapid communications in mass spectrometry, 2008)
The 14 and 70 eV electron ionization mass spectra of five sets (R1 = Me, Et, i‐Pr, t‐Bu and Ph) of seven 2‐aryl‐4‐R1‐substituted (Ar = C6H4X; X = p‐NO2, m‐Br, p‐Cl, H, p‐Me, p‐OMe and p‐NMe2) (1–5) and of seven 2‐aryl‐5‐phenyl‐substituted 1,3‐oxazolidines (6; for Ar, see above) were recorded to study their ring‐chain equilibria in the gas phase. These equilibria were also studied by 1H NMR spectroscopy in CDCl3 for compounds 5 and 6. A few 2,4‐ and 2,5‐dimethyl‐2‐aryl derivatives (7, 8: Ar = C6H4X; X = m‐Br, H and p‐OMe) were studied both in CDCl3 and in the gas phase. The main characteristics of the ring‐chain equilibria expressed by the variable ΣRA% of the ring and of the chain form proved to be a strong dependence on the nature of the substituents on C‐2 and C‐4. The results in the gas phase are compared with those in CDCl3. Copyright © 2008 John Wiley & Sons, Ltd.